NHS for sale: myths, lies and deception - Davis, Jacky; Lister, John; Wrigley, David (Monmouth, 2015)
"This book explains what has been happening to the NHS since the 2012 Act. It challenges myths: that the NHS was broke, that we can't afford the NHS, that doctors and GPs would be in the driving seat; that patients would have more choice, that there would be less bureaucracy and that communities would have greater control. It analyses the effects of new structures and financial pathways. It shows that the private sector is not cheaper. A mass of evidence sustains the authors' arguments and conclusions. The NHS is under massive threat. The authors review the policies of the Coalition and the Labour Party and set out the essential support that the NHS needs. They suggest what can done to promote a healthy NHS."